The effects of oestrogen and progesterone on lymphocyte and plasma cell population in the oviduct and uterine mucosae during follicular and luteal phases in ewes - Abdul Razak, Intan Shameha; Abu Bakar @ Zakaria, Md Zuki; Mohamed Mustapha, Noordin; Haron, Abd Wahid; Tengku Ibrahim, Tengku Azmi (Universiti Putra Malaysia Press, 2011)
Hormonal changes during the oestrous cycle influence the immune cells pattern in ewe's reproductive tract, particularly in the uterus and oviduct. This study was conducted to quantify the number of lymphocytes and plasma cells of the uterus and oviduct under the influences of oestrogen or progesterone. Results showed that the number of lymphocytes in different parts of the uterus was significantly (p<0.05) higher during the follicular phase as compared to the luteal phase. Nevertheless, in the follicular phase group, the number of lymphocytes was not significantly different between the middle and anterior horn, while in the luteal phase group, the number of lymphocytes was not significantly different between the posterior and middle horns. Similarly, the number of plasma cells was significantly (p<0.05) higher in the follicular phase compared to the luteal phase for the different parts of the reproductive tract. In the luteal phase group, on the contrary, the number of plasma cells was not significantly different between the posterior and middle horns and between the anterior horn and oviduct. Thus, the results emphasize that the ewes are much more protected when they are in follicular phase since the number of lymphocytes and plasma cells are higher.